Collective bargaining by objectives : a positive approach - Richardson, Reed C. (Englewood Cliffs, N.J. : Prentice-Hall, 1977)
This book provides a systematic framework for approaching collective bargaining negotiation. The book provides a history of collective bargaining, basic bargaining theories, the legal framework of the negotiation process and what he calls the players to the process: management, labour, and third parties.
Includes bibliographical references and index.
lje 25/01/2018
Loans
Keywords: Collective bargaining--United States; Management